A Transformational and an Authentic Leader Walk into a Bar: Who Feels Included? - Merlini, Katrina P.; Albowicz, Ché; Merlini, Paul G. (Journal of Leadership, Accountability and Ethics, 2019)
Drawing from social information processing theory and social learning theory as theoretical bases, this study examined whether transformational and authentic leadership styles predict perceptions of inclusive environments and whether the styles differ in the relative importance of their prediction. Using multilevel modeling techniques, results demonstrated that both styles independently predict perceptions of inclusive environments. Fit indices were slightly better for the transformational leadership model. Dominance analysis revealed transformational leadership had slightly greater importance in predicting perceptions of inclusive environments. Results suggest both styles are important in predicting perceptions of inclusive environments.